The Environment-Based Learning to Improve Students Achievement on the Concepts of Spermatophyte Diversity - Juairiah Juairiah; Yuswar Yunus; Djufri Djufri (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2014)
The objective of the study is to evolve student achievement on the concept of spermatophyte diversity through environment-based learning. The study was conducted at MAN Rukoh Banda Aceh by implementing environment-based learning through Pre-test and Pos-test group. The population was students of class X year 2013/2014 consisting of 6 parallel classes. The sample was Class X-1 consisting of 28 students.  Data was analysed persentage and t-test. The results showed that there was significant improvement of students achievement (t-count t-table, or 2,499 2.051).  It can be concluded that there was significant increases in student achievement by implementing environment-based learning on the concept of spermatophyte diversity